Tear-resistant BOPET film for solar modules and preparation method thereof

By using a special blend and polyurethane precoat in BOPET film, the problem of poor tear resistance of BOPET film is solved, which significantly improves the toughness and tear resistance of the film and extends the service life of solar cell modules.

CN116426095BActive Publication Date: 2025-03-07JIANGSU YUXING FILM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310345866.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-03-07
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

The existing BOPET films have poor tear resistance and are prone to being torn during use, resulting in damage to the solar cell module.

Method used

BOPET films are prepared by using special blends and pre-coated a layer of polyurethane material on the surface of the film to improve the tear resistance and toughness of the film.

Benefits of technology

Without affecting other performance, the tear resistance and toughness of BOPET films are significantly improved, the risk of tear is reduced, and the service life of solar cell modules is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004159657670000021
    Figure BDA0004159657670000021
  • Figure BDA0004159657670000022
    Figure BDA0004159657670000022
  • Figure BDA0004159657670000051
    Figure BDA0004159657670000051
Patent Text Reader

Abstract

The present invention provides a tear-resistant BOPET film for solar modules and a preparation method thereof, and relates to the technical field of plastic film production and processing. The BOPET film comprises a BOPET base film and a tear-resistant pre-coating material coated on the surface of the BOPET base film; the BOPET base film comprises a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer. The BOPET film for solar modules provided by the present invention greatly improves the toughness and tear resistance of the BOPET film without affecting other properties of the BOPET film through the synergistic effect of the polyester surface layer, the polyester core layer and the tear-resistant coating, thereby greatly reducing the risk of tearing when used in solar modules, avoiding damage to the battery module, and extending the service life of the solar module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic film production and processing, and in particular to a tear-resistant BOPET film for solar modules and a preparation method thereof. Background Art

[0002] Solar cell modules are used to convert solar energy into electrical energy under sunlight. Therefore, solar cell modules are usually installed outdoors and exposed to the natural environment. Since solar cell modules need to operate for many years under various outdoor environmental conditions, the stability and reliability of solar cell modules are very important. In order to improve the stability and reliability of solar cell modules, it is crucial to use high-performance materials to prepare solar cell modules.

[0003] The main components of a solar cell module are a solar cell panel and a film for wrapping the solar cell panel, wherein the film for wrapping the solar cell panel is used to provide support and protection for the solar cell panel.

[0004] BOPET film is used in solar cell modules due to its excellent heat resistance, chemical stability, transparency and mechanical properties. However, due to the insufficient toughness and poor tear resistance of existing BOPET films, they are easily torn during the preparation of solar cell modules, causing damage to the solar cell panels. Summary of the invention

[0005] The technical problem to be solved by the present invention is: in order to solve the problem of poor tear resistance of BOPET film in the prior art, the present invention provides a tear-resistant BOPET film for solar modules. The BOPET film is prepared by adopting a special blend and pre-coated with a layer of polyurethane material on the surface. The tear resistance and toughness of the BOPET film can be improved without affecting other properties, and the risk of tearing can be greatly reduced. Therefore, when the BOPET film is used in a solar cell module, damage to the solar cell module is avoided, the service life of the solar cell module is extended, and the problem of poor tear resistance of the BOPET film in the prior art is solved.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A tear-resistant BOPET film for a solar module, comprising a BOPET base film and a tear-resistant pre-coating material coated on the surface of the BOPET base film;

[0008] The BOPET base film comprises a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer;

[0009] The polyester surface layer comprises the following components in parts by weight:

[0010]

[0011] The polyester core layer comprises the following components in parts by weight:

[0012]

[0013] Optionally, the functional filler toughening agent is prepared according to the following method:

[0014] S101: adding 1040 parts by weight of terephthalic acid, 450-650 parts by weight of ethylene glycol, 0.5-1.0 parts by weight of antimony trioxide, 0.5-1.0 parts by weight of trimethyl phosphate, and 100-150 parts by weight of a modified functional filler dispersion into a reactor, raising the temperature of the reactor to 200-240° C. and the pressure to 0.5-0.6 MPa under a nitrogen atmosphere, and keeping the temperature for 60-90 minutes;

[0015] S102: Raise the temperature in the reactor to 240-250° C. and keep it warm for 90-150 minutes;

[0016] S103: reducing the pressure in the reactor to 200-300 Pa, and then increasing the temperature in the reactor to 260-270° C., and keeping the temperature for 150-180 min;

[0017] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent by melt extrusion granulation.

[0018] Optionally, the modified functional filler dispersion is prepared according to the following method:

[0019] S201: 10-20 parts by weight of the functional filler and 80-90 parts by weight of ethylene glycol are uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 30-60 minutes. After the activation is completed, a vacuum pump is used to filter it clean, and a dryer is used to dry and remove the residual solvent to obtain a dry activated functional filler;

[0020] S202: After preparing a silane coupling agent and anhydrous ethanol into a solution with a mass fraction of 1.5%, 500 mL of the solution is placed in 20 g of dry activated functional filler and stirred for 30-60 min. After standing for 36-48 h, the solution is filtered out using a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0021] S203: Add 10-20 parts by weight of dried modified functional filler, 80-90 parts by weight of ethylene glycol, and 3-5 parts by weight of dispersant into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 800-1000 rpm and a mixing time of 60-90 min to obtain a modified functional filler dispersion.

[0022] Optionally, the functional filler is aluminum nitride or boron nitride.

[0023] Optionally, the silane coupling agent is 3-aminopropyltrimethoxysilane.

[0024] Optionally, the dispersant is polyethylene glycol.

[0025] Optionally, the tear-resistant pre-coating material is prepared according to the following method:

[0026] S301: 50-60 parts by weight of polyurethane and 50-100 parts by weight of acetone are mixed and stirred for 120-240 minutes to obtain a polyurethane dispersion;

[0027] S302: adding 2-5 parts by weight of a cross-linking agent to the polyurethane dispersion, stirring at a temperature of 50-70° C. for 30-60 minutes until the cross-linking agent is completely dissolved, thereby obtaining a tear-resistant pre-coating.

[0028] Optionally, the polyurethane is polyether polyurethane or polyester polyurethane.

[0029] Optionally, the cross-linking agent is a polyol cross-linking agent or an isocyanate cross-linking agent.

[0030] Another object of the present invention is to provide a method for preparing the tear-resistant BOPET film for solar modules as described above, comprising the following steps:

[0031] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0032] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and form an ABA three-layer co-extrusion structure thick sheet by a rotating cooling roller;

[0033] S3: biaxially stretching the thick sheet after preheating, longitudinally stretching it by 2.5-3.5 times and transversely stretching it by 2.5-3.5 times;

[0034] S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 230-250° C. to obtain a BOPET base film;

[0035] S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife;

[0036] S6: Send the coated BOPET base film into a drying oven, dry and solidify the coating by heating and ventilation, the drying temperature is 150-200°C, and the drying time is 60-120min;

[0037] S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

[0038] The beneficial effects of the present invention are:

[0039] The tear-resistant BOPET film for solar modules provided by the present invention greatly improves the toughness and tear resistance of the BOPET film without affecting other properties of the BOPET film through the synergistic effect of the polyester surface layer, the polyester core layer and the tear-resistant coating. Therefore, when used in solar modules, the tearing risk is greatly reduced, damage to the battery module is avoided, and the service life of the solar module is extended. DETAILED DESCRIPTION

[0040] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0041] In order to solve the problem of poor tear resistance of BOPET film in the prior art, the present invention provides a tear-resistant BOPET film for solar modules, wherein the BOPET film comprises a BOPET base film and a tear-resistant pre-coating coated on the surface of the BOPET base film, and a tear-resistant coating is formed on the surface of the BOPET film by the tear-resistant coating; wherein the BOPET base film comprises a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer.

[0042] The polyester surface layer comprises the following components in parts by weight:

[0043]

[0044] The polyester core layer comprises the following components in parts by weight:

[0045]

[0046]

[0047] The present invention first obtains a tear-resistant BOPET base film by combining various materials in a polyester surface layer and a polyester core layer while ensuring properties such as weather resistance and light transmittance, and then prepares a tear-resistant coating on the surface of the tear-resistant BOPET base film by a tear-resistant coating, thereby further improving the toughness of the BOPET film and improving its tear resistance.

[0048] The tear-resistant BOPET film for solar modules provided by the present invention greatly improves the toughness and tear resistance of the BOPET film without affecting other properties of the BOPET film through the synergistic effect of the polyester surface layer, the polyester core layer and the tear-resistant coating. Therefore, when used in solar modules, the tearing risk is greatly reduced, damage to the battery module is avoided, and the service life of the solar module is extended.

[0049] The functional filler toughening agent in the polyester core layer and the polyester surface layer is preferably prepared according to the following method:

[0050] S101: adding 1040 parts by weight of terephthalic acid, 450-650 parts by weight of ethylene glycol, 0.5-1.0 parts by weight of antimony trioxide, 0.5-1.0 parts by weight of trimethyl phosphate, and 100-150 parts by weight of a modified functional filler dispersion into a reactor, raising the temperature of the reactor to 200-240° C. and the pressure to 0.5-0.6 MPa under a nitrogen atmosphere, and keeping the temperature for 60-90 minutes;

[0051] S102: Raise the temperature in the reactor to 240-250° C. and keep it warm for 90-150 minutes;

[0052] S103: reducing the pressure in the reactor to 200-300 Pa, and then increasing the temperature in the reactor to 260-270° C., and keeping the temperature for 150-180 min;

[0053] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.620-0.670 dL / g, a melting point of 250-270°C, an average molecular weight of 25000-35000, and a modified functional filler mass percentage of 1-2% by melt extrusion granulation.

[0054] The present invention introduces a functional filler into a functional filler toughening agent by modifying a functional filler dispersion, and then effectively improves the toughness and tear resistance of the BOPET film through the synergistic effect of the functional filler and the above components.

[0055] Furthermore, the modified functional filler dispersion of the present invention is preferably prepared according to the following method:

[0056] S201: 10-20 parts by weight of the functional filler and 80-90 parts by weight of ethylene glycol are uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 30-60 minutes. After the activation is completed, a vacuum pump is used to filter it clean, and a dryer is used to dry and remove the residual solvent to obtain a dry activated functional filler;

[0057] S202: After preparing a 1.5% solution with a mass fraction of a silane coupling agent and anhydrous ethanol (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution is put into 20 g of dry activated functional filler and stirred for 30-60 min. After standing for 36-48 h, the solution is filtered out with a vacuum pump and dried with a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0058] S203: Add 10-20 parts by weight of dried modified functional filler, 80-90 parts by weight of ethylene glycol, and 3-5 parts by weight of dispersant into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 800-1000 rpm and a mixing time of 60-90 min to obtain a modified functional filler dispersion.

[0059] The modified functional filler dispersion prepared by the above method helps to improve the uniformity of dispersion of the functional filler in the system, improve its compatibility with the system, and further help to synergize with other combinations in the system to improve toughness and tear resistance.

[0060] In the present invention, the preferred functional filler is aluminum nitride or boron nitride, and further preferably the particle size of the functional filler is in the range of 100-500 nm.

[0061] To improve compatibility, the preferred silane coupling agent of the present invention is 3-aminopropyltrimethoxysilane and the dispersant is polyethylene glycol.

[0062] Furthermore, based on the use requirements of solar modules, in order to take into account the conversion efficiency and service life of solar modules, the BOPET film is required to have excellent weather resistance and light transmittance in addition to excellent toughness and tear resistance; in order to take into account the toughness, tear resistance, weather resistance and light transmittance of the BOPET film and make it have excellent comprehensive performance, the preferred opening masterbatch in the polyester surface layer of the present invention is Yizheng Chemical Fiber FG610 slices; the PET polyester slices in the polyester surface layer and the polyester core layer are Yizheng Chemical Fiber FG728 slices, the PEN polyester slices are Japanese Teijin TN8050SC slices, the elastomer is selected from at least one of SIS, SEBS, and SBS, and the anti-ultraviolet agent is selected from at least one of benzoxepinone, fluphenazine, and triazine.

[0063] In order to ensure the tear resistance of the BOPET film, the tear-resistant pre-coating is preferably a polyurethane tear-resistant pre-coating, and the tear-resistant pre-coating is further preferably prepared according to the following method:

[0064] S301: 50-60 parts by weight of polyurethane and 50-100 parts by weight of acetone are mixed and stirred for 120-240 minutes to obtain a polyurethane dispersion;

[0065] S302: adding 2-5 parts by weight of a cross-linking agent into the polyurethane dispersion, stirring at a temperature of 50-70° C. for 30-60 minutes until the cross-linking agent is completely dissolved, thereby obtaining a tear-resistant pre-coating.

[0066] After the tear-resistant pre-coating is coated on the surface of the BOPET base film, a tear-resistant coating is prepared. Through the synergistic effect of the tear-resistant coating, the polyester surface layer and the polyester core layer, the toughness and tear resistance of the BOPET film can be improved while ensuring the weather resistance, light transmittance and other properties of the BOPET film.

[0067] In the present invention, the polyurethane is preferably a polyether polyurethane or a polyester polyurethane; and the cross-linking agent is preferably a polyol cross-linking agent or an isocyanate cross-linking agent.

[0068] Another object of the present invention is to provide a method for preparing the tear-resistant BOPET film for solar modules as described above, the method comprising the following steps:

[0069] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0070] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0071] S3: After preheating, the thick sheet is biaxially stretched to 2.5-3.5 times in the longitudinal direction and 2.5-3.5 times in the transverse direction;

[0072] S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 230-250° C. to obtain a BOPET base film;

[0073] S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife;

[0074] S6: Send the coated BOPET base film into a drying oven, dry and solidify the coating by heating and ventilation, the drying temperature is 150-200°C, and the drying time is 60-120min;

[0075] S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

[0076] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0077] Example 1

[0078] This embodiment provides a tear-resistant BOPET film for a solar module, comprising a BOPET base film, and a tear-resistant pre-coating material coated on the surface of the BOPET base film;

[0079] The BOPET base film includes a polyester core layer and a polyester surface layer coextruded on the upper and lower surfaces of the polyester core layer;

[0080] The polyester surface layer comprises the following components in parts by weight:

[0081]

[0082]

[0083] The polyester core layer comprises the following components in parts by weight:

[0084]

[0085] Among them, the PET polyester chips are FG728 chips from Yizheng Chemical Fiber; the PEN polyester chips are TN8050SC chips from Teijin of Japan; the elastomer is SBS; the anti-ultraviolet agent is triazine anti-ultraviolet agent Mayzo UV 531;

[0086] The preparation process of functional filler toughening agent is as follows:

[0087] S101: Add 1040 parts by weight of terephthalic acid, 500 parts by weight of ethylene glycol, 0.5 parts by weight of antimony trioxide, 0.5 parts by weight of trimethyl phosphate, and 130 parts by weight of modified functional filler dispersion into a reactor, raise the temperature of the reactor to 220° C. and the pressure to 0.5 MPa under a nitrogen atmosphere, and keep the temperature for 90 minutes;

[0088] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0089] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0090] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.650 dL / g, a melting point of 265° C., an average molecular weight of 30,000, and a modified aluminum nitride mass percentage of 1.5% by melt extrusion granulation;

[0091] The modified functional filler dispersion is prepared as follows:

[0092] S201: Surface activation: 15 parts by weight of aluminum nitride (average particle size of 500 nm) and 85 parts by weight of ethylene glycol were uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 45 minutes. After the activation was completed, the mixture was filtered out using a vacuum pump, and then dried in a dryer to remove the residual solvent, thereby obtaining a dry activated functional filler;

[0093] S202: Surface modification: After preparing a 1.5% solution of 3-aminopropyltrimethoxysilane and anhydrous ethanol as a silane coupling agent (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution is put into 20 g of dry activated functional filler and stirred for 45 minutes. After standing for 48 hours, the mixture is filtered out with a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0094] S203: Dispersion: 15 parts by weight of dried modified functional filler, 85 parts by weight of ethylene glycol, and 5 parts by weight of dispersant polyethylene glycol are added into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 1000 rpm for 80 min to obtain a modified functional filler dispersion;

[0095] In this embodiment, the tear-resistant pre-coating material is prepared according to the following method:

[0096] S301: 50 parts by weight of polyether polyurethane JW-2000 and 50 parts by weight of acetone are mixed and stirred for 180 minutes to obtain a polyurethane dispersion;

[0097] S302: adding 5 parts by weight of an isocyanate crosslinking agent HDI to the polyurethane dispersion, stirring at 65° C. for 45 minutes until the crosslinking agent is completely dissolved, to obtain a tear-resistant pre-coating;

[0098] The tear-resistant BOPET film used for solar panels in this embodiment is prepared according to the following method:

[0099] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0100] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0101] S3: After preheating, the thick sheet is biaxially stretched to 3.0 times in the longitudinal direction and 3.0 times in the transverse direction;

[0102] S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 245° C. to obtain a BOPET base film;

[0103] S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife;

[0104] S6: The coated BOPET base film is sent into a drying oven, and the coating is dried and cured by heating and ventilation, with a drying temperature of 180°C and a drying time of 90 minutes;

[0105] S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

[0106] Example 2

[0107] This embodiment provides a tear-resistant BOPET film for a solar module, comprising a BOPET base film, and a tear-resistant pre-coating material coated on the surface of the BOPET base film;

[0108] The BOPET base film includes a polyester core layer and a polyester surface layer coextruded on the upper and lower surfaces of the polyester core layer;

[0109] The polyester surface layer comprises the following components in parts by weight:

[0110]

[0111] The polyester core layer comprises the following components in parts by weight:

[0112]

[0113] Among them, the PET polyester chips are FG728 chips from Yizheng Chemical Fiber; the PEN polyester chips are TN8050SC chips from Teijin of Japan; the elastomer is SIS; the anti-ultraviolet agent is Mayzo UV 326, a benzoxanone anti-ultraviolet agent;

[0114] The preparation process of functional filler toughening agent is as follows:

[0115] S101: Add 1040 parts by weight of terephthalic acid, 450 parts by weight of ethylene glycol, 1.0 parts by weight of antimony trioxide, 1.0 parts by weight of trimethyl phosphate, and 150 parts by weight of a modified functional filler dispersion into a reactor, and raise the temperature of the reactor to 220° C. and the pressure to 0.5 MPa under a nitrogen atmosphere, and keep the temperature for 90 minutes;

[0116] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0117] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0118] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.640 dL / g, a melting point of 260° C., an average molecular weight of 28,000, and a modified aluminum nitride mass percentage of 2.0% by melt extrusion granulation;

[0119] The modified functional filler dispersion is prepared as follows:

[0120] S201: Surface activation: 20 parts by weight of boron nitride (average particle size of 300 nm) and 80 parts by weight of ethylene glycol are uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 45 minutes. After the activation is completed, the mixture is filtered out using a vacuum pump, and then dried in a dryer to remove the residual solvent, thereby obtaining a dry activated functional filler;

[0121] S202: Surface modification: After preparing a 1.5% solution of 3-aminopropyltrimethoxysilane, a silane coupling agent, and anhydrous ethanol (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution is put into 20 g of dry activated functional filler and stirred for 60 min. After standing for 48 h, the mixture is filtered out with a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0122] S203: Dispersion: Add 20 parts by weight of dried modified functional filler, 80 parts by weight of ethylene glycol, and 5 parts by weight of dispersant polyethylene glycol into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 1000 rpm for 90 minutes to obtain a modified functional filler dispersion;

[0123] In this embodiment, the tear-resistant pre-coating material is prepared according to the following method:

[0124] S301: 50 parts by weight of polyester polyurethane MDI-2000 and 50 parts by weight of acetone are mixed and stirred for 180 minutes to obtain a polyurethane dispersion;

[0125] S302: adding 5 parts by weight of a polyol crosslinking agent TMP to the polyurethane dispersion, stirring at 60° C. for 50 minutes until the crosslinking agent is completely dissolved, to obtain a tear-resistant pre-coating;

[0126] The tear-resistant BOPET film used for solar panels in this embodiment is prepared according to the following method:

[0127] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0128] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0129] S3: After preheating, the thick sheet is biaxially stretched to 3.2 times in the longitudinal direction and 3.2 times in the transverse direction;

[0130] S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 245° C. to obtain a BOPET base film;

[0131] S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife;

[0132] S6: The coated BOPET base film is sent into a drying oven, and the coating is dried and cured by heating and ventilation, with a drying temperature of 190°C and a drying time of 80 minutes;

[0133] S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

[0134] Comparative Example 1

[0135] This comparative example provides a BOPET film, which includes a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer;

[0136] The polyester surface layer comprises the following components in parts by weight:

[0137] 10 parts of open masterbatch;

[0138] 75 pieces of PET polyester chips;

[0139] 10 parts of anti-ultraviolet agent;

[0140] The polyester core layer comprises the following components in parts by weight:

[0141] 75 pieces of PET polyester chips;

[0142] 5 parts of anti-ultraviolet agent;

[0143] Among them, the PET polyester chips are FG728 chips from Yizheng Chemical Fiber; the anti-ultraviolet agent is triazine anti-ultraviolet agent Mayzo UV531;

[0144] The BOPET film in this embodiment is prepared as follows:

[0145] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0146] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0147] S3: After preheating, the thick sheet is biaxially stretched to 3.0 times in the longitudinal direction and 3.0 times in the transverse direction;

[0148] S4: The biaxially stretched thick sheet is heat-set at 245° C., cooled, drawn, rolled and slit to obtain a BOPET film.

[0149] Comparative Example 2

[0150] This comparative example provides a BOPET film, including a BOPET base film, and a tear-resistant pre-coating material coated on the surface of the BOPET base film;

[0151] The BOPET base film includes a polyester core layer and a polyester surface layer coextruded on the upper and lower surfaces of the polyester core layer;

[0152] The polyester surface layer comprises the following components in parts by weight:

[0153]

[0154] The polyester core layer comprises the following components in parts by weight:

[0155]

[0156] Among them, the PET polyester chips are FG728 chips from Yizheng Chemical Fiber; the elastomer is SBS; the anti-ultraviolet agent is triazine anti-ultraviolet agent Mayzo UV 531;

[0157] The preparation process of functional filler toughening agent is as follows:

[0158] S101: Add 1040 parts by weight of terephthalic acid, 500 parts by weight of ethylene glycol, 0.5 parts by weight of antimony trioxide, 0.5 parts by weight of trimethyl phosphate, and 130 parts by weight of modified functional filler dispersion into a reactor, raise the temperature of the reactor to 220° C. and the pressure to 0.5 MPa under a nitrogen atmosphere, and keep the temperature for 90 minutes;

[0159] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0160] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0161] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.650 dL / g, a melting point of 265° C., an average molecular weight of 30,000, and a modified aluminum nitride mass percentage of 1.5% by melt extrusion granulation;

[0162] The modified functional filler dispersion is prepared as follows:

[0163] S201: Surface activation: 15 parts by weight of aluminum nitride (average particle size of 500 nm) and 85 parts by weight of ethylene glycol were uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 45 minutes. After the activation was completed, the mixture was filtered out using a vacuum pump, and then dried in a dryer to remove the residual solvent, thereby obtaining a dry activated functional filler;

[0164] S202: Surface modification: After preparing a 1.5% solution of 3-aminopropyltrimethoxysilane and anhydrous ethanol as a silane coupling agent (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution is put into 20 g of dry activated functional filler and stirred for 45 minutes. After standing for 48 hours, the mixture is filtered out with a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0165] S203: Dispersion: 15 parts by weight of dried modified functional filler, 85 parts by weight of ethylene glycol, and 5 parts by weight of dispersant polyethylene glycol are added into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 1000 rpm for 80 min to obtain a modified functional filler dispersion;

[0166] In this embodiment, the tear-resistant pre-coating material is prepared according to the following method:

[0167] S301: 50 parts by weight of polyether polyurethane JW-2000 and 50 parts by weight of acetone are mixed and stirred for 180 minutes to obtain a polyurethane dispersion;

[0168] S302: adding 5 parts by weight of an isocyanate crosslinking agent HDI to the polyurethane dispersion, stirring at 65° C. for 45 minutes until the crosslinking agent is completely dissolved, to obtain a tear-resistant pre-coating;

[0169] The tear-resistant BOPET film used for solar panels in this embodiment is prepared according to the following method:

[0170] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0171] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0172] S3: After preheating, the thick sheet is biaxially stretched to 3.0 times in the longitudinal direction and 3.0 times in the transverse direction;

[0173] S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 245° C. to obtain a BOPET base film;

[0174] S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife;

[0175] S6: The coated BOPET base film is sent into a drying oven, and the coating is dried and cured by heating and ventilation, with a drying temperature of 180°C and a drying time of 90 minutes;

[0176] S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

[0177] Comparative Example 3

[0178] The difference between this comparative example and Example 1 is that no elastomer is added to the BOPET base film.

[0179] Comparative Example 4

[0180] The difference between this comparative example and Example 1 is that no functional filler toughening agent is added to the BOPET base film.

[0181] Comparative Example 5

[0182] The difference between this comparative example and Example 1 is that the functional filler toughening agent in the BOPET base film is prepared according to the following method:

[0183] S101: 1040 parts by weight of terephthalic acid, 500 parts by weight of ethylene glycol, 0.5 parts by weight of antimony trioxide, 0.5 parts by weight of trimethyl phosphate, and 130 parts by weight of aluminum nitride (average particle size of 500 nm) were added to a reactor, and the temperature of the reactor was raised to 220° C. and the pressure was raised to 0.5 MPa under a nitrogen atmosphere, and the temperature was kept for 90 minutes;

[0184] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0185] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0186] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent by melt extrusion granulation.

[0187] Comparative Example 6

[0188] The difference between this comparative example and Example 1 is that the functional filler toughening agent in the BOPET base film is prepared according to the following method:

[0189] S101: Add 1040 parts by weight of terephthalic acid, 500 parts by weight of ethylene glycol, 0.5 parts by weight of antimony trioxide, 0.5 parts by weight of trimethyl phosphate, and 130 parts by weight of modified functional filler dispersion into a reactor, raise the temperature of the reactor to 220° C. and the pressure to 0.5 MPa under a nitrogen atmosphere, and keep the temperature for 90 minutes;

[0190] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0191] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0192] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.650 dL / g, a melting point of 265° C., an average molecular weight of 30,000, and a modified aluminum nitride mass percentage of 1.5% by melt extrusion granulation;

[0193] The modified functional filler dispersion is prepared as follows:

[0194] S201: Surface modification: After preparing a 1.5% solution of 3-aminopropyltrimethoxysilane and anhydrous ethanol (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution was added to 20 g of aluminum nitride (average particle size of 500 nm) and stirred for 45 min. After standing for 48 h, the solution was filtered out using a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0195] S202: Dispersion: Add 15 parts by weight of dried modified functional filler, 85 parts by weight of ethylene glycol, and 5 parts by weight of dispersant polyethylene glycol into a high-speed mixer for uniform dispersion and mixing. The dispersion speed is 1000 rpm and the mixing time is 80 min to obtain a modified functional filler dispersion.

[0196] Comparative Example 7

[0197] The difference between this comparative example and Example 1 is that the aluminum nitride in step S201 is replaced by calcium oxide.

[0198] Comparative Example 8

[0199] The difference between this comparative example and Example 1 is that carbon fiber is used to replace the aluminum nitride in step S201.

[0200] Comparative Example 9

[0201] This comparative example provides a BOPET film, which includes a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer;

[0202] The polyester surface layer comprises the following components in parts by weight:

[0203]

[0204] The polyester core layer comprises the following components in parts by weight:

[0205]

[0206] Among them, the PET polyester chips are FG728 chips from Yizheng Chemical Fiber; the PEN polyester chips are TN8050SC chips from Teijin of Japan; the elastomer is SBS; the anti-ultraviolet agent is triazine anti-ultraviolet agent Mayzo UV 531;

[0207] The preparation process of functional filler toughening agent is as follows:

[0208] S101: Add 1040 parts by weight of terephthalic acid, 500 parts by weight of ethylene glycol, 0.5 parts by weight of antimony trioxide, 0.5 parts by weight of trimethyl phosphate, and 130 parts by weight of modified functional filler dispersion into a reactor, raise the temperature of the reactor to 220° C. and the pressure to 0.5 MPa under a nitrogen atmosphere, and keep the temperature for 90 minutes;

[0209] S102: Raise the temperature in the reactor to 245° C. and keep it warm for 120 min;

[0210] S103: reducing the pressure in the reactor to 250 Pa, and then increasing the temperature in the reactor to 260° C., and keeping the temperature for 180 min;

[0211] S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent with a viscosity of 0.650 dL / g, a melting point of 265° C., an average molecular weight of 30,000, and a modified aluminum nitride mass percentage of 1.5% by melt extrusion granulation;

[0212] The modified functional filler dispersion is prepared as follows:

[0213] S201: Surface activation: 15 parts by weight of aluminum nitride (average particle size of 500 nm) and 85 parts by weight of ethylene glycol were uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 45 minutes. After the activation was completed, the mixture was filtered out using a vacuum pump, and then dried in a dryer to remove the residual solvent, thereby obtaining a dry activated functional filler;

[0214] S202: Surface modification: After preparing a 1.5% solution of 3-aminopropyltrimethoxysilane and anhydrous ethanol as a silane coupling agent (the mass fraction of the silane coupling agent in the solution is 1.5%), 500 mL of the solution is put into 20 g of dry activated functional filler and stirred for 45 minutes. After standing for 48 hours, the mixture is filtered out with a vacuum pump and dried in a dryer to remove the residual solvent to obtain a dry modified functional filler;

[0215] S203: Dispersion: 15 parts by weight of dried modified functional filler, 85 parts by weight of ethylene glycol, and 5 parts by weight of dispersant polyethylene glycol are added into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 1000 rpm for 80 min to obtain a modified functional filler dispersion;

[0216] The BOPET film in this embodiment is prepared as follows:

[0217] S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion;

[0218] S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet;

[0219] S3: After preheating, the thick sheet is biaxially stretched to 3.0 times in the longitudinal direction and 3.0 times in the transverse direction;

[0220] S4: The biaxially stretched thick sheet is heat-set at 245° C., cooled, drawn, rolled and slit to obtain a BOPET film.

[0221] Comparative Example 10

[0222] The difference between this comparative example and Example 1 is that the polyamide polyester AH-1502E13 is used to replace the polyether polyurethane JW-2000 in step S301.

[0223] Comparative Example 11

[0224] The difference between this comparative example and Example 1 is that the polyether polyurethane JW-2000 in step S301 is replaced by acrylate D9683.

[0225] Comparative Example 12

[0226] The difference between this comparative example and Example 1 is that, in parts by weight, the polyester surface layer comprises the following components:

[0227]

[0228] The polyester core layer comprises the following components in parts by weight:

[0229]

[0230]

[0231] The performance tests were performed on the BOPET films prepared in Examples 1-2 and Comparative Examples 1-11, respectively, and the test methods were as follows:

[0232] Mechanical strength: tested in accordance with GB / T 13542.2-2021;

[0233] Elongation at break: tested in accordance with GB / T 13542.2-2021;

[0234] Tear resistance: tested by right angle tear tester;

[0235] Weather resistance: After PCT aging (121℃*100%RH*2atm*48h), the elongation at break was tested;

[0236] Transparency: Tested in accordance with ASTM D1003.

[0237] The test results are shown in Table 1:

[0238] Table 1

[0239]

[0240] It can be seen from the above data that the BOPET prepared in each embodiment of the present invention has excellent weather resistance, transparency, mechanical properties and tear resistance, which proves that the BOPET film provided by the present invention greatly improves the toughness and tear resistance of the BOPET film without affecting other properties of the BOPET film, so that when used in solar modules, the risk of tearing can be greatly reduced, damage to the battery module can be avoided, and the service life of the solar module can be extended.

[0241] Compared with Example 1, Comparative Example 1 does not add PEN polyester chips, elastomers, and functional filler toughening agents to the BOPET base film, and no tear-resistant coating is added subsequently; the mechanical properties, tear resistance, and weather resistance of the BOPET film provided in this comparative example are significantly worse than those of Example 1; at the same time, although a functional filler toughening agent is added to Example 1, the effect on the transparency of the BOPET film is minimal;

[0242] Compared with Example 1, in Comparative Example 2, no PEN polyester chips are added to the BOPET base film; the mechanical properties, tear resistance and weather resistance of the BOPET film provided in this comparative example are slightly lower than those of Example 1;

[0243] Compared with Example 1, no elastomer is added to the BOPET base film in Comparative Example 3; the mechanical properties, tear resistance and weather resistance of the BOPET film provided in this comparative example are slightly lower than those of Example 1;

[0244] Compared with Example 1, no functional filler toughening agent is added to the BOPET base film in Comparative Example 4; the mechanical strength of the BOPET film provided in this comparative example is slightly lower than that of Example 1, and the elongation at break, tear resistance, and weather resistance are significantly reduced;

[0245] Comparative Example 5 Compared with Example 1, during the preparation of the functional filler toughening agent added to the BOPET base film, the functional filler was not surface activated and surface modified; the addition of the functional filler toughening agent to the BOPET film provided in this comparative example not only did not improve its mechanical properties, but instead caused a further decrease in its mechanical properties, and its transparency was also slightly decreased;

[0246] Compared with Example 1, in the preparation process of the functional filler toughening agent added to the BOPET base film, only the functional filler was subjected to surface modification treatment, and no surface activation treatment was performed; although the performance of the BOPET film provided by this comparative example was slightly improved compared with that of Comparative Example 5, it was still significantly decreased compared with that of Example 1;

[0247] Comparative Example 7 Compared with Example 1, calcium oxide is used to replace the functional filler aluminum nitride; the BOPET film provided in this comparative example has significantly poor mechanical properties, weather resistance and transparency due to improper use of the functional filler;

[0248] Compared with Example 1, Comparative Example 8 replaces the functional filler aluminum nitride with carbon fiber; the mechanical properties and weather resistance of the BOPET film provided by this comparative example are slightly lower than those of Example 1, and the transparency is significantly reduced;

[0249] Compared with Example 1, Comparative Example 9 did not prepare a tear-resistant coating; the mechanical properties and weather resistance of the BOPET film provided in this comparative example were slightly lower than those of Example 1;

[0250] Compared with Example 1, in Comparative Example 10, the tear-resistant pre-coating material is a polyamide coating; the mechanical properties and weather resistance of the BOPET film provided by this comparative example are slightly lower than those of Example 1;

[0251] Compared with Example 1, the tear-resistant pre-coating in Comparative Example 11 is an acrylic coating; the mechanical properties and weather resistance of the BOPET film provided by this comparative example are slightly lower than those of Example 1, and the transparency is significantly reduced.

[0252] Compared with Example 1, Comparative Example 12 increases the amount of PEN polyester chips added to the base film; the mechanical properties and weather resistance of the BOPET film provided by this comparative example are slightly reduced, while the weather resistance is significantly reduced.

[0253] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A tear-resistant BOPET film for solar panels, characterized in that: It comprises a BOPET base film, and a tear-resistant pre-coating material coated on the surface of the BOPET base film; The BOPET base film comprises a polyester core layer and a polyester surface layer co-extruded on the upper and lower surfaces of the polyester core layer; The polyester surface layer comprises the following components in parts by weight: 10-15 parts of open masterbatch; 50-60 pieces of PET polyester chips; 10-15 pieces of PEN polyester chips; Elastomer 10-15 parts; 10-15 parts of anti-ultraviolet agent; 5-10 parts of functional filler toughening agent; The polyester core layer comprises the following components in parts by weight: 60-70 pieces of PET polyester chips; 15-20 pieces of PEN polyester chips; Elastomer 10-15 parts; 5-10 parts of anti-ultraviolet agent; 5-10 parts of functional filler toughening agent; The functional filler toughening agent is prepared according to the following method: S101: adding 1040 parts by weight of terephthalic acid, 450-650 parts by weight of ethylene glycol, 0.5-1.0 parts by weight of antimony trioxide, 0.5-1.0 parts by weight of trimethyl phosphate, and 100-150 parts by weight of a modified functional filler dispersion into a reactor, raising the temperature of the reactor to 200-240° C. and the pressure to 0.5-0.6 MPa under a nitrogen atmosphere, and keeping the temperature for 60-90 minutes; S102: Raise the temperature in the reactor to 240-250° C. and keep it warm for 90-150 minutes; S103: reducing the pressure in the reactor to 200-300 Pa, and then increasing the temperature in the reactor to 260-270° C., and keeping the temperature for 150-180 min; S104: removing small molecular impurities in the reaction system by distillation, and finally obtaining a functional filler toughening agent by melt extrusion granulation; The modified functional filler dispersion is prepared according to the following method: S201: 10-20 parts by weight of the functional filler and 80-90 parts by weight of ethylene glycol are uniformly dispersed and mixed, and then placed in a plasma treatment instrument for surface activation for 30-60 minutes. After the activation is completed, a vacuum pump is used to filter it clean, and a dryer is used to dry and remove the residual solvent to obtain a dry activated functional filler; S202: After preparing a silane coupling agent and anhydrous ethanol into a solution with a mass fraction of 1.5%, take 500 mL and put it into 20 g of dry activated functional filler and stir for 30-60 minutes. After standing for 36-48 hours, use a vacuum pump to filter it clean, and use a dryer to dry to remove the residual solvent to obtain a dry modified functional filler; S203: adding 10-20 parts by weight of dried modified functional filler, 80-90 parts by weight of ethylene glycol, and 3-5 parts by weight of dispersant into a high-speed mixer for uniform dispersion and mixing at a dispersion speed of 800-1000 rpm for a mixing time of 60-90 min to obtain a modified functional filler dispersion; The functional filler is aluminum nitride or boron nitride; The tear-resistant pre-coating material is prepared as follows: S301: 50-60 parts by weight of polyurethane and 50-100 parts by weight of acetone are mixed and stirred for 120-240 minutes to obtain a polyurethane dispersion; S302: adding 2-5 parts by weight of a cross-linking agent to the polyurethane dispersion, stirring at a temperature of 50-70° C. for 30-60 minutes until the cross-linking agent is completely dissolved, thereby obtaining a tear-resistant pre-coating.

2. The tear-resistant BOPET film for solar modules according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltrimethoxysilane.

3. The tear-resistant BOPET film for solar modules according to claim 1, characterized in that: The dispersant is polyethylene glycol.

4. The tear-resistant BOPET film for solar modules according to claim 1, characterized in that: The polyurethane is polyether polyurethane or polyester polyurethane.

5. The tear-resistant BOPET film for solar modules according to claim 1, characterized in that: The cross-linking agent is a polyol cross-linking agent or an isocyanate cross-linking agent.

6. A method for preparing a tear-resistant BOPET film for solar modules according to any one of claims 1 to 5, characterized in that: The steps include: S1: According to the formula, the polyester surface layer material is transported to the extruder A for melt extrusion; the polyester core layer material is transported to the extruder B for melt extrusion; S2: Melt-extrude the molten polyester surface layer material and the polyester core layer material through a three-layer co-extrusion die head, and use a rotating cooling roller to form an ABA three-layer co-extrusion structure thick sheet; S3: biaxially stretching the thick sheet after preheating, longitudinally stretching it by 2.5-3.5 times and transversely stretching it by 2.5-3.5 times; S4: heat setting, cooling, winding and slitting the biaxially stretched thick sheet at 230-250° C. to obtain a BOPET base film; S5: Coat the tear-resistant pre-coating on the surface of the BOPET base film by using the pressure of the coating roller and the coating of the coating knife; S6: Send the coated BOPET base film into a drying oven, dry and solidify the coating by heating and ventilation, the drying temperature is 150-200°C, and the drying time is 60-120min; S7: Cooling the dried BOPET base film through a cooling roller to reduce its surface temperature to below room temperature, so that the coating is completely cured to obtain a BOPET film for a solar cell module.

Citation Information

Patent Citations

  • High-barrier polyester film and its preparation method

    CN102225648A

  • High temperature-resistant polyester film and preparation method thereof

    CN109054311A